Impactos da gestão pela qualidade total sobre os resultados econômico-financeiro de uma instituição bancária (Banco Comercial de médio porte): um estudo de caso. - Neves, Edson Pimenta (2002)
In the world of today an actual application of the strategy in the businesses is fundamental for the success of any enterprise. The Strategic Planning is being implanted in the companies, seeking to maintenance of the managerial activity and the obtaining of market earnings with result economic-financial. With the globalization of the economy, the competition increased, considerably, because the businesses don t have more limits and the distance between the nations no more represents difficulty. The author of this dissertation, through specialized bibliography Iooked for what there s of more modern in the Strategic Planning, in this case study. For so much, it used knowledge in the areas of the Total Quality and of the economical analysis techniques-financial. Demonstrated that, through the Strategic Planning, the Bank Financial Institution (commercial Bank) it can increase the economical results and to win market among your competitors. The indcators obtained in the analysis of the Financial Demonstrations (Patrimonial Balances and Demonstrations of the Result) compared, they take to the reach of the objectives and the execution of the planned goals. The Strategic Planning with base in Balanced Scorecard is a modern technique of administration. The study developed by the researcher it signaled so that new researches are made, being applied Balanced Scorecard, in the administration of the competitive businesses.